Serum magnesium levels in preterm labour in relation to socio-economic status - Anand, Shifali; Jaggi, Rohini; Bala, Nerrupham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Serum magnesium level in pregnancy is a valuable tool to find out preterm onset of labour. In the asymptomatic group, greater surveillance and administration of steroids, tocolytics and transfer to a higher centre. In this study, low maternal serum magnesium level was associated with preterm labour. The values were also lower in women with low socio-economic status. Methods: The subjects included 100 pregnant women with preterm labour (cases) between 28 and 37-week gestation (group A) and similar number of pregnant women with term labour (controls) between 37 and 40 weeks (group B). Inclusion criteria for cases was singleton pregnancy, painful uterine contractions more than two in 30 minutes, intact fetal membranes, cervical dilatation (at least 1 cm) and effacement (80%). Serum magnesium levels were done in both the groups. Patients were followed until delivery. Routine antenatal investigations were done. Serum levels of magnesium were estimated by Erba’s semi auto-analyser. Results: 62% patients in group A were from rural areas. More patients in group A (70%) were from low socioeconomic class. More women in group A were anaemic (44%). Mean value of hemoglobin in group A was 9.93 g/dl. More patients in group A had muscle cramps (89%). VLBW (<1500 g) neonates were more in group A (21%). Also, LBW (1500-2499 g) neonates were more in group A (60%). Mean neonatal birth weight in group A (1907.3 g) was less. Neonatal morbidity and mortality were observed significantly more in group A. Mean serum magnesium was less in group A. Conclusions: Low maternal serum magnesium level is associated with preterm labour. Patients with preterm labour have significantly low serum magnesium level when compared with labour at term. The values were also lower in women with low socioeconomic status.